2021
DOI: 10.4269/ajtmh.20-1069
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Insecticidal Nets Incorporating Piperonyl Butoxide Reduce the Risk of Malaria in Children in Western Kenya: A Cluster Randomized Controlled Trial

Abstract: Malaria vectors have acquired an enzyme that metabolizes pyrethroids. To tackle this problem, we evaluated long-lasting insecticidal nets incorporating piperonyl butoxide (PBO-LLINs) with a community-based cluster randomized control trial in western Kenya. The primary endpoints were anopheline density and Plasmodium falciparum polymerase chain reaction (PCR)-positive prevalence (PCRpfPR) of children aged 7 months to 10 years. Four clusters were randomly selected for each of the treatment and control arms (eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The findings of a subsequently published cluster-randomised trial conducted in western Kenya in 2009-11 were consistent with these conclusions; parasite prevalence measured by PCR in children aged 7 months to 10 years was significantly lower at 5 and 12 months post-LLIN distribution in clusters that received PBO LLINs (Olyset Plus) compared with conventional LLINs (Olyset Net). 30 Considering the available data, in April 2021, WHO's Vector Control Advisory Group concluded that PBO LLINs are more effective than conventional non-PBO LLINs in areas with high-level pyrethroid resistance in malaria mosquito vectors, confirming the public health value of PBO LLINs. 31 In conclusion, we found that PBO LLINs provide superior protection against malaria prevalence and vector abundance 25 months post-distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of a subsequently published cluster-randomised trial conducted in western Kenya in 2009-11 were consistent with these conclusions; parasite prevalence measured by PCR in children aged 7 months to 10 years was significantly lower at 5 and 12 months post-LLIN distribution in clusters that received PBO LLINs (Olyset Plus) compared with conventional LLINs (Olyset Net). 30 Considering the available data, in April 2021, WHO's Vector Control Advisory Group concluded that PBO LLINs are more effective than conventional non-PBO LLINs in areas with high-level pyrethroid resistance in malaria mosquito vectors, confirming the public health value of PBO LLINs. 31 In conclusion, we found that PBO LLINs provide superior protection against malaria prevalence and vector abundance 25 months post-distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical malaria incidences were high among school-aged children aged 5-14 years in all study zones, according to the findings. Lower bednet usage among school-aged children exposes them to high mosquito bites at night, which may explain why clinical malaria incidences are higher in this age group [34,39,40]. The low infection rate among children under the age of five compared to school-age children could be attributed to the children being cared for by their parents and sleeping under mosquito nets at night [12,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…PBO inhibits the enzymes that break down pyrethroids. Previous studies have demonstrated the increased insecticidal effect of Olyset®Plus when compared with the standard LLINs, even in areas where pyrethroid-resistant mosquitoes were widely reported (20)(21)(22).…”
Section: Background and Rationale {6a}mentioning
confidence: 99%